Revisiting History: Shakespeare’s Revisionist View of the Crusades and Crusading - Mufeed F. Al-Abdullah (An Overview of Literature, Language and Education Research Vol. 8, 2024)
This chapter examines the theme of crusades and crusading in Shakespeare’s King John, Richard II, Henry IV, and Henry V in relation to the medieval religious, political, and historical backgrounds of Elizabethan England during the Reformation. It studies Shakespeare’s revisionist perspectives on that medieval historical phenomenon and shows how he handles the major points of the matter with some latitude he gleaned from the cultural perspective formed after his nation had sailed away from medieval politics and ideas. Shakespeare examines the past and assesses the holy wars fought against Muslims in the Holy Land. Shakespeare argues that the crusades against the Muslims in the Near East had a disastrous effect on Europe and its citizens. In order to offer further light on the plays’ historical backgrounds and Shakespeare’s perspective on those well-known medieval events, the current study will examine these three concerns as they are presented in Shakespeare’s biographies. The researcher employs the method of contextual analysis of the provided pertinent texts related to those campaigns in Shakespeare’s ten history plays. The study comes to the conclusion that in his reassessment of these medieval military campaigns, the Elizabethan playwright emphasizes three key issues: he first illustrates the terrible consequences of the Third Crusade against England under King John. Second, he illustrates the difficulties that followed the return of the European nations that took part in the renowned Third Crusade. Third, he raises questions about the true intentions behind the campaigns against the East and the disobedient European nations. The chapter aims to demonstrate how Shakespeare’s mistrust of the military expeditions to the East foreshadows contemporary cynicism regarding the true motivations of the religious and political leaders who led those expeditions.